IR IMAGING AND VIBRATORY METHODS OF CONTROL AND DIAGNOSTICS OF THE EQUIPMENT AT OJSC «BSW – MANAGEMENT COMPANY OF HOLDING «BMC» - A. S. Shinkarev; E. V. Gapeenko (Литьë и металлургия)
The article discusses the main methods of diagnostics of the equipment of OJSC «BSW – management company of holding «BMC». Presents results of diagnostics of various equipment with the description of the devices directly used for the diagnostic that can detect various defects of the equipment at the stage of their origination. Describes the advantages of these methods compared to other methods of control and diagnostics.